Pendampingan Radiografer dalam Quality Control Pengujian Kolimator di Instalasi Radiologi RS Bhayangkara Semarang - Rosidah, Siti; Jamil, Masfufatun; Suraningsih, Nanik (Universitas Pahlawan Tuanku Tambusai, 2024)
One of the quality assurance programs is collimator testing on X-ray aircraft. According to KMK no. 1250 of 2009 Collimator testing on Sinr-X aircraft is carried out once a month. The Bhayangkara Hospital Radiology Installation already has a quality assurance program for radiography equipment, however collimator testing on aircraft is not carried out routinely, most recently in August 2020 when the X-ray aircraft was installed and when licensing was to be carried out. The service team wants to provide conformity testing services related to collimator testing and provide motivation to partners to routinely carry out equipment quality control programs through socialization and assistance in conformity testing of X-ray aircraft collimators in accordance with KMK No. 1250 concerning quality control. The research results show that a quality control program for X-ray aircraft already exists but has not been carried out routinely, the results of collimator field area testing experienced deviations that were still within the normal limit below the standard, namely less than 2%. To ensure that the X-ray aircraft is in good condition and to ensure that the radiation dose to the patient does not occur again, a quality control program should be carried out periodically.